Conservation Based Disaster Resilient Schools in Realizing Legal Protection from Disaster Risks in Magelang Regency - Suwandoko; Rizza Arge Winanta; Rodiyah; Suhadi; Ali Masyhar (Indonesian State Law Review (ISLRev), 2026)
Magelang Regency is a region with a high level of disaster vulnerability, as recorded by the Regional Disaster Management Agency in 2020-2024, showing several disasters that occurred, including landslides, earthquakes, extreme weather, building fires, forest fires, droughts, volcanic eruptions, and floods. This situation demands concrete steps in disaster mitigation, especially for vulnerable groups such as children. Children are not physically and mentally prepared to face disasters, and their knowledge of disaster risk reduction is still limited. Schools are strategic places to build preparedness while providing legal protection for children in emergency situations. This study aims to analyze the urgency of establishing disaster resilient schools as a mitigation strategy and analyze the concept of conservation based disaster resilient schools to realize legal protection from disaster risks in Magelang Regency. The research method used is empirical juridical research. The results of the research on the urgency of disaster resilient schools as disaster mitigation in Magelang Regency are seen from the aspect of Pancasila, especially the 5th principle. The sociological aspect is that there are 106 Elementary Schools and 21 Junior High Schools located in disaster prone zones, while legally supported by various regulations related to formulating disaster resilient schools. The concept of conservation based disaster resilient schools realizes legal protection from disaster risks in Magelang Regency, namely by integrating elements of legal protection and conservation principles to realize sustainable legal protection for all school residents in facing potential disasters in Magelang Regency. The conclusion of the study shows the urgency of having disaster resilient schools and the concept of conservation based disaster resilient schools that integrate legal protection as a guarantee of safety and sustainability of children's educational rights in disaster prone areas. Suggestions for the need a synergistic relationship between schools in Magelang Regency, the Magelang Regency Education Office, and the Magelang Regency Regional Disaster Management Agency in the formation of conservation based disaster responsible schools as an effort to provide legal protection from disaster risks.